2009
DOI: 10.2118/129745-pa
|View full text |Cite
|
Sign up to set email alerts
|

Combined Underground Gas Storage and Enhanced Oil Recovery in a Fractured Reservoir

Abstract: The Schönkirchen Tief reservoir is located in the Vienna basin. The reservoir contained 19 std m 3 oil originally in place. The current recovery factor after 45 years of production is 59%. The field was produced by water injection. The wells, located at the crest of the high relief structure are exhibiting a high water cut. In 2006-07, a comprehensive study was performed to optimize the future development of the field.The field is made up of different types of dolostones. The lower part of the field consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…From outcrop studies and analysis of the production behavior, a vertical fracture spacing of approximately 3 m was determined [for more details, see de Kok and Clemens (2009)]. …”
Section: Field Casementioning
confidence: 99%
See 2 more Smart Citations
“…From outcrop studies and analysis of the production behavior, a vertical fracture spacing of approximately 3 m was determined [for more details, see de Kok and Clemens (2009)]. …”
Section: Field Casementioning
confidence: 99%
“…An integrated study showed that sufficient working volume can be achieved and some incremental oil might be recovered (de Kok and Clemens 2009). The Schönkirchen Tief reservoir is characterized by a high-permeability-fracture and a lower-permeability-matrix system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation